(3QSGdI CadGWhf GdMcje Edi ahajQjhS aj MbjbI faj GdZe hGdge hEKHGJ GdRgO LhGHkG Yf SDGd cGf SHb efg Edjg (B- (3haj PjdgG JYdjb dajKGZhQSs - (3GadGWhf GdMcjes
(3ChdgG (B:s
(3HSe Gddg Gdedc GdMb hGdEdg GdUGOb GdeSei HdZGJ GdEaJQGb GdebUhO HGdEJaGb GdbOje GdPi de jRd efTF eHGOF GdMQcGJ GdChdi NGdb GdCVOGO ai GdCUdGM hGdEaSGO s
(3BNQgG (B:s
(3hef SeY GdhYX hGdMceI Ke de jYed HgG cGfG TGgOjf Ydjg hgh eMLhL HgeG hGdSdGe JeJ GdQSGdI hGdMb ddg Mb MeOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs